PENERAPAN METODE ARAS DALAM PEMILIHAN LOKASI REHABILITASI TAMBANG TIMAH DI KEPULAUAN BANGKA BELITUNG - Nurhaeka Tou; Putri Mentari Endraswari; Iski Zaliman; A. Taqwa Martadinata; Marhasi Putri (LPPM UNIVERSITAS BINA INSAN, 2026)
Determining the priority for the rehabilitation of former tin-mining land is still done manually, so the assessment process is time-consuming and can introduce subjectivity into decision-making. Differences in land conditions based on several criteria make the process of determining rehabilitation priorities more complex, so a system capable of providing objective and structured recommendations is needed. This study aims to develop a Decision Support System (DSS) using the ARAS (Additive Ratio Assessment) method to determine rehabilitation priorities for former tin mining land. The ARAS method is used through the stages of determining criteria and weights, normalizing the decision matrix, calculating utility values, and ranking alternative land areas. The results show that the system is able to generate rehabilitation priority recommendations in accordance with the results of manual calculations, and helps the decision-making process become more effective and efficient. Testing using the Mean Absolute Percentage Error (MAPE) method yielded an error of 13.3%, which falls within the good category. These results indicate that the system has a fairly high level of accuracy in supporting the determination of rehabilitation priorities for former tin mining land.